Pengaruh Depurasi Terhadap Konsentrasi Logam Berat Timbal (Pb) dan Kadmium(Cd) dalam Jaringan Lunak Kerang Darah (Anadara granosa) - Setiawan, Alam; Yulianto, Bambang; Wijayanti, Diah Permata (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
Blood Cockle (Anadara granosa) is one type of shellfish which have an important economic value in Indonesia. Semarang waters is one of the location of the Blood Cockle which were allegedly tainted by Pb and Cd. The metal content could be reduced by depuration. This research purposed to determine the content of heavy metal concentrations in Semarang waters and determine the effect of shell length and the length of depuration time on the heavy metal concentrations of Pb and Cd in the A. granosa. This research was conducted on 23 July to 28 August 2010. The method used in this study is description on the preliminary research and laboratory experimental method for depuration. Preliminary research was performed by testing the concentration of heavy metals in water, sediments and soft tissue of A. granosa in the waters of Semarang. Primary research conducted depuration process based on differences size of the scallop shell length â‰¥ 2.0 cm and < 2.0 cm, and different time depuration treatment, i.e. control (without depuration), 1 day, 3 day, 5 day, and 7 days. According to AAS test results showed, the highest concentrations of Pb and Cd heavy metals in Semarang water respectively at 0.23 ppm and 0.036 ppm, in sediment 1.48 ppm and 0.091 ppm, and in the soft tissues of A. granosa of 0.82 ppm and 0.042 ppm. Depuration process can reduce the content of heavy metal concentrations of Pb and Cd, respectively at 0.37 ppm and 0.051 ppm.